Pengaruh Kemudahan Penggunaan dan Gaya Hidup Terhadap Perilaku Konsumtif Pengguna Shopee Paylater di Kalangan Gen Z di Kota Tanjungpinang - Reza Ariyanto; Catri Jintar; Siti Arita Novia (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of Ease of Use and Lifestyle on the consumption behaviour of Shopee PayLater users among Gen Z in Tanjungpinang City. The research design is explanatory quantitative, with sampling conducted using purposive sampling (96 respondents). Primary data were collected through a Likert-scale questionnaire, supplemented by secondary data from the literature; all data were analysed using SPSS version 27. The data analysis stages included instrument validity testing, testing of classical assumptions, multiple linear regression analysis, t-tests, F-tests, and the Coefficient of Determination (R²). The results of the study indicate that the variables Ease of Use (X1) and Lifestyle (X2) jointly have a positive and significant effect on Consumption Behaviour (Y). This is evidenced by a calculated F-value of 22.185, which is greater than the critical F-value (3.09), as well as a p-value of <0.001, which is less than 0.05. Ease of Use and Lifestyle together drive the consumer behaviour of Shopee PayLater users. Ease of use makes users feel that transactions are more practical and convenient, while Gen Z’s lifestyle which is closely tied to trends, promotions, and popular products further strengthens the urge to shop. Based on these results, Gen Z is advised to manage their finances more wisely, while Shopee is encouraged to improve transparency and financial education. Future research is recommended to include additional variables such as self-control and financial literacy.